2016
DOI: 10.1002/glia.22976
|View full text |Cite
|
Sign up to set email alerts
|

Association between cytoplasmic CRABP2, altered retinoic acid signaling, and poor prognosis in glioblastoma

Abstract: Retinoic acid (RA), a metabolite of vitamin A, is required for the regulation of growth and development. Aberrant expression of molecules involved in RA signaling has been reported in various cancer types including glioblastoma multiforme (GBM). Cellular retinoic acid-binding protein 2 (CRABP2) has previously been shown to play a key role in the transport of RA to retinoic acid receptors (RARs) to activate their transcription regulatory activity. Here, we demonstrate that CRABP2 is predominantly located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 77 publications
2
37
0
1
Order By: Relevance
“…It has been proposed that CRABP-II and FABP5 are signicant prognostic factors associated with poor survival in certain cancers such as glioblastoma and breast cancer. 32,33 Our results show that the expression levels of CRABP-II and FABP5, in both classic and large-cell MBs, were signicantly higher than those in nodular MBs. Due to the classic and large-cell histological subtypes presenting worse clinical outcomes than the nodular subtype, up-regulated CRABP-II and FABP5 may be related to prognosis in MB patients.…”
Section: Discussionmentioning
confidence: 68%
“…It has been proposed that CRABP-II and FABP5 are signicant prognostic factors associated with poor survival in certain cancers such as glioblastoma and breast cancer. 32,33 Our results show that the expression levels of CRABP-II and FABP5, in both classic and large-cell MBs, were signicantly higher than those in nodular MBs. Due to the classic and large-cell histological subtypes presenting worse clinical outcomes than the nodular subtype, up-regulated CRABP-II and FABP5 may be related to prognosis in MB patients.…”
Section: Discussionmentioning
confidence: 68%
“…The potential molecular mechanism of GFAP promoting the aggressiveness of GBM is also important. Liu et al revealed that retinoic acid (RA) and its derivatives, initiate RA-linked signaling transductions and induce chemotherapy sensitivity in GBM [ 15 ]. Moreover, changes of cellular RA balance in GBM might also be related to changes of GFAP expression and phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Semiquantitative RT-PCR was used to verify differential expression of selected PKCs in U87 control and B-FABP-transfected cells as well as in GBM cell lines that are either negative (T98, U87, A172, CLA, and M021) or positive (U251, U373, M049, M103, and M016) for B-FABP [ 12 , 31 , 32 ]. Sources of GBM cell lines have been described previously [ 33 ] and they are as follows: T98, from Walter Nelson-Rees, Naval Biomedical Research Station, Oakland, CA, USA; U87, U251, and U373, from Jorgen Fogh, Sloane Kettering Institute, Rye, NY, USA; A172, from Stuart A. Aaronson, NCI, Bethesda, MD, USA; CLA, from Paul Kornblith, Albert Einstein College of Medicine, Montefiore Medical Center, Bronx, NY, USA. M016, M021, M049, and M103 GBM cell lines were obtained from Drs.…”
Section: Methodsmentioning
confidence: 99%